The role of coherent flow structures in the sensible heat fluxes of an Alaskan boreal forest. Issue 15 (1st August 2013) - Starkenburg, Derek; Fochesatto, Gilberto J.; Prakash, Anupma; Cristóbal, Jordi; Gens, Rudiger; Kane, Douglas L.
Abstract : [1] Accelerations in the flow over forests generate coherent structures which locally enhance updrafts and downdrafts, forcing rapid exchanges of energy and matter. Here, observations of the turbulent flow are made in a highly heterogeneous black spruce boreal forest in Fairbanks, Alaska at 2.6 h (12 m) and 0.6 h (3 m), where h is the mean canopy height of 4.7 m. Wavelet analysis is used to detect coherent structures. The sonic temperature and wind data cover 864 half‐hour periods spanning winter, spring, and summer. When mean global statistics of structures are analyzed at the two levels independently, results are similar to other studies. Specifically, an average of eight structures occurs per period, their mean duration is 85 s, and their mean heat flux contribution is 48%. However, this analysis suggests that 31% of the structures detected at 2.6 h, and 13% at 0.6 h, may be influenced by wave‐like flow organization. Remarkably, less than 25% of the structures detected occur synchronously in the subcanopy and above canopy levels, which speaks robustly to the lack of flow interaction within only nine vertical meters of the forest. Key Points: Coherent structures in Alaskan boreal forest are similar to other sites 30% of the structures above the canopy may be influenced by gravity waves Most coherent structures are confined to one level in this Alaskan boreal forest